Training Need Assessment for Core Competencies of Agricultural Extension Personnel in Kerala: An Analytical Study (Indian Journal of Extension Education, 2018)
Training need can be defined as the condition having perceived difference between ’what is’ and ’what should be’ in terms of knowledge, core competency skills and attitudes so that these gaps or needs can be fulfilled, in order to enable the extension personnel to perform their roles more effectively in their work organizations. Three training institutions: Community Agrobiodiversity Center (working under an NGO), SAMETI (working under State Department) and CTI (under State Agricultural University) were chosen for the study. Purposive and Random Sampling were carried out for the study. The sample consisted of trainees from three different training institutes.Four different training programmes related to core competency development being organized during 2017-18 were selected purposively from each of the three training institutes. Fifteen trainees for each training programmes were selected randomly with a sample size of sixty from each institute making one hundred eighty trainees as total sample size. Questionnaire was developed for the study. Personal interview and focus group discussion methods were also used as tools for data collection. Eight core competencies were chosen for this study viz., communication skills, subject matter expertise, professionalism, programme planning and implementation, leadership skills, resource mobilization, Information Communication Technologies (ICT), and managerial ability for developing the Training Need Index (TNI) and Skill gap analysis. ANOVA test revealed that there is significant difference between core competencies in different training institutes. Post hoc test with Duncan revealed that there is significant difference between three institutes in case of five core competencies communication ability, professionalism, programme planning and implementation, leadership skills and managerial ability.